On the TYPP of the tongue : Advanced Master of Research in Art and Design, 2019-2020. - Dumalin, Caroline; Gorus, Kim; Kubat, Zeynep; Petrešin-Bachelez, Nataša; Slater, Marnie; Van Brabandt, Petra (Antwerp : St Lucas School of Arts Antwerp / KdG, 2020)
Felipe Muhr: The Iguanodon Monologues ; Lucy Cordes Engelman: Skype to Landline ; Alicia Jeannin: A: Did you feel something particular at the beginning of the confinement, in relation to the need for... B: Word, action, engagement... ; Pierre-Antoine Vettorello: A Conversation with Diana Bamimeke and Rima Hamid ; Risk Hazekamp: Versatile Relationality ; Anna Housiada: Social Skin: An Exchange of Thoughts with Kat'ytaya Catitu Tayassu ; Paz Ortúzar: Absolute Bodies ; Agata Jastrząbek Filarowska: And the Word became Flesh ; Anne Marie Sampaio: Words are Actions: On the Repulsion that Moves Us ; Simona Da Pozzo: Voices from Bronze and Stone ; Tunde Toth: Circling Conversations: The Fragility of Distanced Dialogues ; Kaat Van Doren: Between Bitumen and Sunlight
boek